ORIGINALITY OF TRANSLATION OF UZBEK FOLK TALES INTO ENGLISH - Sharobidinova Shahlo (Journals Park Publishing, 2023)
The objective of this paper is twofold: to present an authentic collaborative project devoted to the transcreation of different versions of Uzbek legends and folk tales, as well as to demonstrate the advantages of applying the transcreative approach to translation in translator training at MA level. The project in question was accomplished in the academic year 2021/2022 by a team of the 1st and 2nd year MA students, partly out of the classroom in an authentic setting and partly within the frames of a specialized collaborative translation course. The paper presents a new idea to teach translation, based on action research and the out-of-the-classroom approach to translator training, and includes a qualitative research case study of students’ views on the project as well as some pedagogical implications, such as the proposal to introduce collaborative transcreation activities into translator training curricula.
Keywords: ethnocultural norms, collaborative translation, folk tale, analysis of folklore, lexical transformations.